Adherence to COVID-19 preventive measures among male medical students, Egypt - Haytham Mahmoud Ahmed (SpringerOpen, 2022)
Abstract Background Adherence to COVID-19 preventive measures is essential for disease control especially given the lack of effective treatment at the time of data collection. Medical students' adherence to COVID-19 preventive measures is highly important because they are at a higher risk of infection as they spend considerable time at hospitals for training. In addition, they will be responsible for disease fighting in the future. This study aimed to identify the adherence to COVID-19 preventive measures among the studied male students of Al-Azhar Faculty of Medicine, Egypt. Methods An online survey was conducted on a convenience sample of 537 male medical students of Al-Azhar University at the Cairo branch between March 2 and April 15, 2021, using an Arabic questionnaire constructed by Google form with link sharing to students' groups on WhatsApp and face book applications. Results A total of 537 students voluntarily submitted their responses. Most of these students were aged between 18 and 20 years (62.4%), rural residents (62.9%), having family income of 5000 LE or less/month (64.2%), studying at the first, second, and sixth years (79.2%). The prevalence of adherence to COVID-19 preventive measures among studied students was 28.1% without significant difference in the students' adherence status regarding age, residence, family income, studying year, or academic score. Wearing a face mask outside the house was practiced by 58% of students, avoiding hugging or kissing others (41.3%), and keeping a distance from others (20.7%). Conclusion Students showed a low level of adherence to COVID-19 preventive measures among students. Also, there is no significant difference between students' adherence status in relation to their socio-economic or academic variables. This unhealthy behavior increases the risk of infection among students. Also, students become a source of infection for their vulnerable contacts. More studies are needed to identify the real cause of this low level of adherence.